2014
DOI: 10.1007/s12020-014-0480-y
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of liraglutide against ER stress in the liver of high-fat diet-induced insulin-resistant rats

Abstract: The purpose of this study was to investigate whether the glucagon-like peptide-1 (GLP-1) analog liraglutide can alleviate endoplasmic reticulum (ER) stress and insulin resistance (IR) in the liver of high-fat diet-induced insulin-resistant rats. Eighty-five male Sprague-Dawley rats were fed with normal chow or a high-fat diet for 12 weeks. The IR was evaluated using the hyperinsulinemic-euglycemic clamp technique. The rats in the HF group were further divided into four groups and were treated with or without l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 41 publications
1
20
0
Order By: Relevance
“…This is the first time to prove that exenatide ameliorates lipid‐induced hepatic ER stress to improve lipid deposition in hepatocytes both in vivo and in vitro . In support of our findings, a previous study showed that liraglutide protected against ER stress in the livers of HFD‐induced insulin‐resistant rats . These findings collectively reveal the ability of GLP‐1 receptor agonists to protect against ER stress and hepatic steatosis.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This is the first time to prove that exenatide ameliorates lipid‐induced hepatic ER stress to improve lipid deposition in hepatocytes both in vivo and in vitro . In support of our findings, a previous study showed that liraglutide protected against ER stress in the livers of HFD‐induced insulin‐resistant rats . These findings collectively reveal the ability of GLP‐1 receptor agonists to protect against ER stress and hepatic steatosis.…”
Section: Discussionsupporting
confidence: 91%
“…In support of our findings, a previous study showed that liraglutide protected against ER stress in the livers of HFD-induced insulin-resistant rats. (32) These findings collectively reveal the ability of GLP-1 receptor agonists to protect against ER stress and hepatic steatosis. Moreover, our study validated that exenatide (exendin-4) alleviated hepatic ER stress in a SIRT1-dependent manner by using genetic or pharmacological SIRT1 inhibition both in vivo and in vitro.…”
Section: Discussionmentioning
confidence: 87%
“…Stimulation of glucagon‐like peptide‐1 (GLP‐1) receptor by a GLP‐1 analogue can activate AMPKα and suppress ER stress (Shao et al , ; Yang et al , ). Furthermore, there is considerable evidence for an important role of GLP‐1R in cardiovascular actions.…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al showed that liraglutide can improve glucose metabolism and insulin resistance in diabetic KKAy mice by stimulating insulin secretion, increasing glycogen production and glycolysis, and up-regulating GLUT4 expression [32]. Numerous studies have shown that endoplasmic reticulum stress is an important pathway for the induction and development of insulin resistance, and previous studies have confirmed the inevitable role of GLP-1 analogues in combating insulin resistance and endoplasmic reticulum stress [33]. In addition, studies have shown that weight loss can improve insulin resistance, reduce insulin secretion requirements, and may improve the effects of glucose and lipotoxicity on pancreatic beta cells [34].…”
Section: Discussionmentioning
confidence: 99%